Marching exercise on balance and blood pressure among Thai community-dwelling older adults at risk of falling - Boonsa-ard, Wittawat; Chompoopan, Worawut (International Journal of Public Health Science (IJPHS), 2024)
Falls are a major cause of death among older people, and they are becoming a bigger problem as people lose their balance. A quasi-experimental study was conducted to examine the effects of marching exercises on the balance abilities of community-dwelling Thai seniors at risk of collapsing. Thirty-five participants were randomly assigned to the experimental or control group. The experimental group engaged in a 12-week marching exercise program that included a continuous foot-turning phase. The control group did not engage in any form of exercise. Compared to the control group, the experimental group demonstrated significant improvements in their ability to maintain their balance. The experimental group's timed up and go test (TUG) score decreased by 3.54 seconds, 95%CI: (2.13 to 4.95), p<0.001 while the functional reach test (FRT) score increased by 4.80 centimeters, 95%CI: (2.34 to 7.25), p<0.001. The systolic blood pressure decreased by 8.62 mmHg, the diastolic blood pressure by 6.48 mmHg, and the heart rate by 4.04 beats per minute. These findings imply that regular marching exercise may improve balance in at-risk older adults. Further research is necessary to clarify the effects of marching exercise on people diagnosed with chronic diseases.